Characterization of a novel Plasmodium falciparum merozoite surface antigen and potential vaccine target - Niaré, Karamoko; Chege, Timothy; Rosenkranz, Micha; Mwai, Kennedy; Saßmannshausen, Zoe; Odera, Dennis; Nyamako, Lydia; Tuju, James; Alfred, Tiono; Waitumbi, John N.; Ogutu, Bernhards; Sirima, Sodiomon B.; et al. (Frontiers in Immunology, 2023)
Detailed analyses of genetic diversity, antigenic variability, protein localization and immunological responses are vital for the prioritization of novel malaria vaccine candidates. Comprehensive approaches to determine the most appropriate antigen variants needed to provide broad protection are challenging and consequently rarely undertaken. Here, we characterized the genetic diversity of ARMA, which we named Asparagine-Rich Merozoite Antigen (ARMA) based on the nature of its sequence, localization and immunogenicity, and found marked differences in population structure between isolates from Africa versus Asia. African isolates shared 34 common haplotypes, including a dominant pair, and the overall selection pressure was directional (Tajima’s D = -2.57; Fu and Li’s F = -9.69; P <0.02). ARMA was localized to the merozoite surface, IgG antibodies induced Fc-mediated degranulation of natural killer cells and strongly inhibited parasite growth in vitro. We analyzed IgG and IgM responses against the common variants of ARMA in independent prospective cohort studies in Burkina Faso (N = 228), Kenya (N = 252) and Mali (N = 195) using a custom microarray, Div-KILCHIP. We found profound serological diversity, but IgG and IgM responses were highly correlated and a hierarchical clustering analysis identified only three major serogroups. Protective IgG and IgM antibodies appeared to target both cross-reactive and distinct epitopes across variants. However, combinations of IgG and IgM antibodies against selected variants were associated with complete protection against clinical episodes of malaria. Our systematic strategy exploits genomic data to deduce the handful of antigen variants with the strongest potential to induce broad protection and may be broadly applicable to other complex pathogens for which effective vaccines remain elusive.